Method for preparing orally disintegrating tablet containing sustained-release pellet core and effectively improving hardness of orally disintegrating tablet

By controlling the humidity range and tableting pressure during the preparation process of multi-unit pellet tablets, and using maltose or maltitol as the granulation binder, the problems of coating layer breakage and poor friability and hardness were solved and achieved Improvement of tablet hardness and friability and optimization of drug dissolution.

CN119326729APending Publication Date: 2025-01-21CHINA RESOURCES DOUBLE CRANE PHARMA COMPANY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411446933.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing multi-unit micro-pellet tablets are prone to breaking the coating layer under high production pressure, while under low production pressure, there are problems of poor fragility and hardness, which affects the drug release effect.

Method used

By compressing tablets in the humidity range of 40 to 70%, drying for 12 to 96 hours after tableting, using maltose or maltitol as the granulation binder, and controlling the tableting pressure between 1 and 4KN to improve Tablet hardness and friability.

Benefits of technology

In the case of not destroying the function of the coating layer, it improves the hardness and jacket of the tablets, enhances the dissolution effect of the drug, and improves the reproducibility and simple operation of the preparation method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087973630000091
    Figure BDA0005087973630000091
  • Figure BDA0005087973630000101
    Figure BDA0005087973630000101
  • Figure BDA0005087973630000111
    Figure BDA0005087973630000111
Patent Text Reader

Abstract

The invention belongs to the field of pharmaceutical preparations, and particularly relates to an oral rapidly disintegrating tablet composition containing a sustained-release pellet core, a preparation method and a method for effectively improving the hardness of tablets. The invention provides a method for improving the hardness of tablets, which comprises the following steps of: granulating and tabletting raw materials containing maltose and / or maltitol in an environment with the humidity of 40-70%, and placing in an environment with the relative humidity of below 10% for 12-96 hours. According to the method, the hardness of the tablet containing one or more functional coating layers can be improved under the condition of low-pressure tabletting through a simple environment control means, and the functional coating layers are not damaged. The method can be achieved only by controlling the environment humidity in the production process, redundant operation steps are reduced, and the production efficiency is improved. The invention further provides a tamsulosin hydrochloride orally disintegrating sustained-release tablet and a preparation method thereof. The tamsulosin hydrochloride orally disintegrating sustained-release tablet is simple to prepare, the process is stable and controllable, and the hardness can be well improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations, and in particular relates to a method for preparing an orally disintegrating tablet containing a sustained-release pellet core and effectively improving the hardness thereof. Background Art

[0002] Multi-unit pellet preparations not only provide new ideas for the development of fast-acting preparations, but also open up new ways for clinical medication for special patients with chronic diseases who need long-term medication. They are especially suitable for children, the elderly, patients with mental illness or dysphagia who are unwilling to cooperate, and personnel who need to work in special environments. They can make up for the limitations of ordinary oral administration for such patients to a certain extent, and are the research direction for future development. In addition, multi-unit pellet tablets are evenly distributed in the gastrointestinal tract after oral administration, which improves bioavailability, avoids gastrointestinal irritation caused by excessive local concentration of drugs, avoids dose burst, and the dose can be divided. After division, the original enteric effect can still be maintained, making it more convenient to take and improving patient compliance. In recent years, with the increase in the number of drugs in this dosage form, more and more drugs have been developed into orally disintegrating tablets. As of July 2020, there are more than 60 related products listed abroad, and more than 30 products have been approved for listing in my country, of which there are only a handful of multi-unit pellet tablets.

[0003] However, for multi-unit microcapsule tablets, due to the presence of multiple functional coating layers, problems such as coating layer breakage and low active ingredient loading rate may occur in subsequent tableting processes, resulting in unsatisfactory drug efficacy. The pellet coating described in CN108066304A is based on the physical and chemical properties that the tamsulosin raw material is poorly soluble in water and methanol and slightly soluble in ethanol. When water is used as a solvent, the coating rate of the active substance cannot be guaranteed, and it takes a longer time to achieve a good coating effect, which cannot achieve the purpose of saving time in industry. In addition, the use of methanol and water to dissolve the raw material and hydroxypropyl methylcellulose claimed in CN1473035B is not friendly to operators and the environment. At the same time, excessive pressure during tableting will cause the functional coating film to break. For example, in CN 108066305A, a pressure that can make the tablet reach a hardness of 3 to 7 kg is directly applied on the tablet press to press the mixed particles into tablets. This direct strong pressure method will cause the sustained-release coating and enteric coating to break, affecting the drug release effect, while lower pressure will make it difficult for the tablets to meet basic indicators such as friability and hardness.

[0004] Therefore, it is necessary to develop a tablet preparation method that does not destroy the function of the coating layer, but can improve the hardness and friability of the tablet and has an excellent dissolution effect, so as to overcome the problem that the existing multi-unit micropellet tablets cause the coating layer to break under high tableting pressure, and have poor friability and hardness under low tableting pressure. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a tablet preparation method which does not destroy the function of the coating layer, can improve the hardness and friability of the tablet, and has excellent dissolution effect, good preparation reproducibility and simple operation.

[0006] In order to solve this technical problem, the purpose of the first aspect of the present invention is to provide a method for improving the hardness, friability and dissolution effect of tablets.

[0007] The second aspect of the present invention is to provide an orally disintegrating sustained-release tablet of tamsulosin hydrochloride.

[0008] The third aspect of the present invention is to provide a method for preparing tamsulosin hydrochloride orally disintegrating sustained-release tablets.

[0009] In order to achieve the above-mentioned purpose of the present invention, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a method for improving tablet hardness, comprising the following steps:

[0011] The tablets are compressed at a humidity range of 40 to 70% and dried for 12 to 96 hours after compression.

[0012] The tablet contains maltose, maltitol and a combination thereof.

[0013] The tabletting pressure is 1-4 KN.

[0014] According to a preferred embodiment of the present invention, the tabletting pressure is 1.5-2.5 KN.

[0015] According to a preferred embodiment of the present invention, the maltose and maltitol are located in the outermost layer of the tablet.

[0016] Preferably, the drying time after tableting is 18 to 96 hours.

[0017] The principle of hardness improvement of the present invention is:

[0018] During the tableting process, the particles are placed in a high humidity environment, and maltose or maltitol is slightly moistened to allow maltose / maltitol to have a certain amount of free water, so that it still has a certain adhesive effect during the tableting process. After the tablets are formed, they are placed in a dry environment. After the free water in the maltose / maltitol is evaporated and dried, a solid bridge with a certain strength is formed, so the hardness of the tablets can be further improved. However, due to the limited free water available from maltose in this process and the limitation of the auxiliary materials used in the tablets themselves, the hardness of the tablets can be increased in the subsequent placement process. It is limited, but it is enough to meet the performance that it should have as an orally disintegrating tablet. Therefore, the present invention actually achieves unexpected technical effects through the coordinated cooperation of various raw and auxiliary materials.

[0019] In the first aspect of the present invention, the inventors found in a large number of experiments that composite tablets with one or more functional coatings may have the problem of functional coating layer rupture during direct compression, resulting in loss of sustained release effect. Therefore, through a large amount of creative work, the inventors found a technical effect of improving the hardness of tablets with one or more functional coatings by only selecting specific raw and auxiliary materials and controlling temperature and humidity, without the need for high tablet pressure and complex instruments and processes for improving hardness.

[0020] In some embodiments of the present invention, the drying refers to reducing the ambient humidity to 10% and below, including 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, and 10%.

[0021] In some embodiments of the present invention, the excessive tableting pressure is specifically 4 KN or more, excluding 4 KN. Preferably, the excessive pressure is 5 KN or more.

[0022] In order to reflect the technical effect of the method for improving tablet hardness of the first aspect of the present invention, the second aspect of the present invention takes tamsulosin as an example to provide a tamsulosin hydrochloride orally disintegrating sustained-release tablet.

[0023] The orally disintegrating sustained-release tablet of tamsulosin hydrochloride comprises a pill core, a sustained-release layer, an enteric layer, and granulation excipients.

[0024] The drug-containing pellet core comprises tamsulosin, a carrier and a drug binder.

[0025] The tamsulosin includes tamsulosin hydrochloride.

[0026] The sustained-release layer comprises a sustained-release material and a pore-forming agent, and the sustained-release layer is wrapped on the drug-containing pill core to obtain a sustained-release pill core.

[0027] The enteric layer comprises an enteric material, a plasticizer and an anti-adhesive agent, and the enteric layer is wrapped on the sustained-release pill core to obtain the enteric pill core.

[0028] The granulation auxiliary materials include fillers, disintegrants, lubricants and granulation binders.

[0029] The granulation binder comprises maltose or a combination of its derivatives.

[0030] Preferably, the maltose derivative comprises at least one of a hydrogenation product, a dehydrogenation product and an oxidation product of maltose.

[0031] Preferably, the hydrogenation product of maltose comprises maltitol.

[0032] Preferably, the dehydrogenation product of maltose comprises maltoseketone.

[0033] Preferably, the oxidation product of maltose comprises maltobionate.

[0034] The tamsulosin hydrochloride orally disintegrating sustained-release tablet adopts the method for improving hardness of the first aspect of the present invention.

[0035] According to a preferred embodiment of the present invention, the enteric-coated pill core comprises, by weight, 5 to 15 parts of tamsulosin, 300 to 600 parts of a carrier, and 10 to 25 parts of a drug binder; the sustained-release layer comprises, by weight, 20 to 55 parts of a sustained-release material and 5 to 20 parts of a pore-forming agent; and / or the enteric layer comprises, by weight, 350 to 1000 parts of an enteric material, 5 to 30 parts of a plasticizer, and 1 to 10 parts of an anti-adhesive agent.

[0036] In some embodiments of the present invention, the enteric-coated pellet core comprises, by weight, 6 to 12 parts of tamsulosin hydrochloride, 300 to 600 parts of a carrier, 12 to 24 parts of a binder, 24.73 to 49.47 parts of a sustained-release material, 7.07 to 14.13 parts of a pore-forming agent, 466.42 to 932.8 parts of an enteric material, 11.67 to 23.31 parts of a plasticizer, and 3.89 to 7.77 parts of an anti-adhesive agent.

[0037] According to a preferred implementation method of the present invention, the granulation auxiliary material layer includes 300-550 parts of filler, 20-65 parts of granulation binder, 2-8 parts of disintegrant, and 2-5 parts of lubricant by weight. The mass ratio of the granulation auxiliary material to the enteric-coated pellet core is 60-120:700-1200.

[0038] According to a preferred embodiment of the present invention, the carrier includes at least one of microcrystalline cellulose, starch, dextrin, mannitol, and anhydrous calcium hydrogen phosphate.

[0039] According to a preferred embodiment of the present invention, the drug adhesive comprises at least one of hypromellose, hydroxypropyl cellulose and polyvinyl pyrrolidone.

[0040] According to a preferred embodiment of the present invention, the sustained-release material includes at least one of ethyl cellulose, cellulose acetate and polyacrylic acid resin.

[0041] According to a preferred embodiment of the present invention, the porogen includes at least one of hydroxypropyl methylcellulose, hydroxypropyl cellulose and polyvinyl pyrrolidone.

[0042] According to a preferred embodiment of the present invention, the enteric material includes at least one of Aquacoat, Eudragit L30D55 ​​and Eudragit NM30D.

[0043] According to a preferred embodiment of the present invention, the plasticizer includes at least one of triethyl citrate, diethyl phthalate, tributyl citrate, dibutyl sebacate, polyethylene glycol, and glyceryl mono- and distearate.

[0044] According to a preferred embodiment of the present invention, the anti-sticking agent comprises talc.

[0045] According to a preferred embodiment of the present invention, the filler includes at least one of mannitol and lactose.

[0046] According to a preferred embodiment of the present invention, the disintegrant comprises cross-linked carboxymethyl cellulose sodium.

[0047] According to a preferred embodiment of the present invention, the lubricant includes sodium stearyl fumarate.

[0048] According to a preferred embodiment of the present invention, the hardness of the tamsulosin hydrochloride orally disintegrating sustained-release tablets is 4.5-5.0 kp.

[0049] According to a preferred embodiment of the present invention, the friability of the tamsulosin hydrochloride orally disintegrating sustained-release tablets is 0% (100 revolutions).

[0050] According to a preferred embodiment of the present invention, the tablet weighs 200 mg and contains 0.2 mg of tamsulosin.

[0051] In the second aspect of the present invention, the lubricant selected by the present invention is sodium stearyl fumarate. During the experiment, the present invention found that hydrophilic sodium stearyl fumarate has better dissolution effect and disintegration performance than other lubricants such as magnesium stearate, calcium stearate, etc.

[0052] The third aspect of the present invention provides a method for preparing the tamsulosin hydrochloride orally disintegrating sustained-release tablets according to the second aspect of the present invention, comprising the following steps:

[0053] 1) dissolving the active ingredient of the pill core and the drug binder in a mixture of ethanol and water, coating the carrier to obtain the pill core;

[0054] 2) dissolving the sustained-release material and pore-forming agent of the sustained-release layer in a mixture of ethanol and water, coating the drug-containing pill core to obtain a sustained-release pill core;

[0055] 3) dispersing the enteric material, plasticizer and anti-adherent agent of the enteric layer in water, coating the sustained-release pellet core to obtain the enteric-coated pellet core;

[0056] 4) placing the filler, disintegrant and enteric-coated pellet core in the granulation excipients in a fluidized bed, adding the granulation binder solution for granulation, sieving the granules, adding the lubricant for mixing, and tableting;

[0057] 5) Drying.

[0058] The steps 1) to 4) are carried out in an environment with a relative humidity of 40 to 70%.

[0059] The tamsulosin includes tamsulosin hydrochloride.

[0060] Preferably, the volume of ethanol in the ethanol-water mixture is 60-90%; more preferably, it is 70-90%.

[0061] According to a preferred embodiment of the present invention, the drying comprises placing the tamsulosin hydrochloride orally disintegrating sustained-release tablets in an environment with a relative humidity of less than 10% for 12 to 96 hours.

[0062] According to a preferred embodiment of the present invention, the coating method comprises a wurster bottom spray method.

[0063] According to a preferred embodiment of the present invention, in step 1), the mass ratio of ethanol to water is (4-5):1.

[0064] According to a preferred embodiment of the present invention, in step 2), the mass ratio of ethanol to water is (30-35):1.

[0065] According to a preferred embodiment of the present invention, in step 1), the inlet air temperature of the coating is 50-60°C, and the inlet air volume is 50-65m 3 / h, the spray liquid volume is 3g / min, the atomization pressure is 1.5bar, and the material temperature is 35℃.

[0066] According to a preferred embodiment of the present invention, in step 2), the inlet air temperature of the coating is 60-70°C, and the inlet air volume is 45m 3 / h, the spray liquid volume is 4g / min, the atomization pressure is 1.5bar, and the material temperature is 35-40℃.

[0067] According to a preferred embodiment of the present invention, in step 3), the inlet air temperature of the coating is 40°C, and the inlet air volume is 40-50m 3 / h, the spray liquid volume is 3g / min, the atomization pressure is 1.5-2.0bar, and the material temperature is 28℃.

[0068] According to a preferred embodiment of the present invention, in step 4), the inlet air temperature of the coating is 70°C, and the inlet air volume is 35-55m 3 / h, spray liquid volume is 25g / min, atomization pressure is 1.0bar, material temperature is 28-30℃, spray cycle: spray 2min, dry 2min.

[0069] According to a preferred embodiment of the present invention, the tableting is performed using a rotary tablet press with a main pressing force of 1 to 4 KN and a filling depth of 6.5 to 7.8 mm.

[0070] In the third aspect of the present invention, the inventors found in a large number of experiments that the prior art uses pure water as a solvent system, which may cause problems such as poor solubility of tamsulosin hydrochloride in water and low utilization rate of active drugs. In addition, auxiliary materials such as ethyl cellulose have poor solubility in pure water and cannot achieve a sustained release effect. The original drug uses a methanol-water system, but methanol has high biological toxicity, which is not conducive to actual production. In the third aspect of the present invention, the inventors have devoted a lot of creative work and found that the solubility of tamsulosin hydrochloride can be significantly increased after compounding ethanol and water. Tamsulosin hydrochloride was originally extremely insoluble in ethanol and had low solubility in water, but after compounding ethanol and water, a solubility far higher than that of single ethanol or water was achieved, which is an unexpected technical effect. Therefore, the present invention selects ethanol-water as a solvent system to replace the pure water system in the prior art, thereby achieving a higher drug application rate and a better sustained release effect.

[0071] In the three aspects of the present invention, the pill cores are not limited in shape, and tablets in spherical, quasi-spherical, ellipsoidal, cylindrical and other shapes all fall within the protection scope of the present invention.

[0072] The beneficial effects achieved by the present invention are:

[0073] The present invention provides a method for improving the hardness and friability of an orally disintegrating tablet containing a functional coating layer pellet core, which has good dissolution effect, excellent reproducibility, convenient operation and is environmentally friendly. Specifically, the raw and auxiliary materials containing maltose and / or maltitol are granulated in a humidity environment of 40% to 70%, tableted and dried for at least 12 to 96 hours, which can simultaneously achieve the effects of protecting the pellet core functional coating and enhancing the physical properties of the tablet.

[0074] The specific beneficial effects are as follows:

[0075] 1. Choosing ethanol and water as solvents has the advantages of being friendly to operators and the environment and having good drug application effect. This is because the water solubility of raw and auxiliary materials including tamsulosin hydrochloride and ethyl cellulose is poor. When water is used as a solvent, the drug application rate of the active substance cannot be guaranteed, and it takes a longer time to achieve the purpose of a good coating effect, and the purpose of saving time in industry cannot be achieved. The present invention finds that tamsulosin hydrochloride is originally extremely insoluble in ethanol and has a low solubility in water, but after ethanol and water are compounded, a much higher solubility is achieved than single ethanol or water, which is an unexpected technical effect. This method uses an ethanol-water solution for preparation, which can guarantee the drug application rate and sustained-release effect.

[0076] 2. When the pellets are tableted, excessive pressure will cause the pellet coating film to break. By adopting this technical solution, tableting can be completed without excessive main pressure, and the hardness and friability of the tablets meet the requirements.

[0077] 3. Compared with other lubricants such as magnesium stearate, calcium stearate, etc., the present invention uses a hydrophilic lubricant sodium stearyl fumarate. The disintegration time of the orally disintegrating tablet prepared using sodium stearyl fumarate is significantly improved and the dissolution effect is excellent.

[0078] 4. In the granulation and tableting process of the present invention, the hardness of the tablet can be improved by only controlling the humidity of the environment, without the need for other cumbersome operating steps, and without the use of equipment such as a constant temperature and humidity chamber. The operation is convenient, the production efficiency is improved, and the disintegration time, friability, reproducibility and dissolution effect are excellent.

[0079] 5. The tablet preparation method provided by the present invention has been subjected to multiple reproducibility experiments, and the tablets obtained have good reproducibility and exhibit consistent physical properties and dissolution rates.

[0080] The method can improve the hardness of tablets containing one or more functional coating layers under low-pressure tablet compression by simple environmental control means without destroying the functional coating layer of the pill core. The orally disintegrating tablet has a high pill core drug application rate, and the friability and disintegration time of the orally disintegrating tablet are improved, and the tablet has excellent disintegration performance and excellent sustained-release effect.

[0081] The method can be implemented by simply controlling the ambient humidity during the production process, which greatly reduces unnecessary operation steps and further improves production efficiency. Based on the method, the present invention further provides a tamsulosin hydrochloride orally disintegrating sustained-release tablet and a preparation method thereof. The tamsulosin hydrochloride orally disintegrating sustained-release tablet is simple to prepare, has a stable and controllable process, and can achieve a good hardness improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] Figure 1 The dissolution results of the reference reagent of Comparative Example 1 and the sustained-release pellet core of Example 2 in a pH 6.8 medium.

[0083] Figure 2 The dissolution results of the reference reagent of Comparative Example 1 and the enteric-coated pellet core of Example 3 in a pH 6.8 medium are shown.

[0084] Figure 3 The dissolution results of the reference reagent of Comparative Example 1 and the enteric-coated pellet core of Example 3 in a pH 1.2 medium are shown.

[0085] Figure 4 The results show the effect of different ambient humidity on tablet hardness.

[0086] Figure 5The results show the effect of different environmental humidity on tablet disintegration time.

[0087] Figure 6 The moisture content changes at different stages from the end of granulation to the placement of finished tablets

[0088] Figure 7 The comparison results of tablet hardness and friability between Example 4 and Example 7 are shown.

[0089] Figure 8 The dissolution results of the reference reagent of Comparative Example 1, the tablet of Example 4 and the powder direct compression tablet of Comparative Example 2 in a pH 6.8 medium are shown.

[0090] Fig. 9 The dissolution results of the reference reagent of Comparative Example 1, the tablet of Example 4 and the powder direct compression tablet of Comparative Example 2 in a pH 1.2 medium are shown.

[0091] Fig.10 These are the maltose crystal form test results of Example 4, Comparative Example 4, and Comparative Example 5 tablets.

[0092] Fig.11 The results show the effect of different granulation binders on tablet hardness.

[0093] Fig.12 The dissolution results of tablets under different main compression pressures in pH 6.8 medium.

[0094] Fig.13 The dissolution results of tablets under different main compression pressures in pH 1.2 medium. DETAILED DESCRIPTION

[0095] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0096] The source information of the raw materials used in the present invention is as follows:

[0097] Tamsulosin hydrochloride (RA CHEM PHARMA LIMITED), microcrystalline cellulose pellets (manufactured by JRS, Germany, D90 is about 200 μm), hydroxypropyl methylcellulose (DuPont, USA), ethyl cellulose (DuPont, USA), talc (Guangxi Longsheng Huamei Talc Development Co., Ltd.), ethyl cellulose aqueous dispersion (Aquacoat ECD-30, DuPont, USA), methacrylic acid-ethyl acrylate copolymer aqueous dispersion (Eudragit L30D55, Evonik, Germany), ethyl acrylate-methyl methacrylate copolymer aqueous dispersion (Eudragit NM30D, Evonik, Germany), triethyl citrate (Senfilx, Morimura Shoji Co., Ltd.), mannitol (Roquette Management (Shanghai) Co., Ltd.), lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), maltose (Hunan Jiudian Hongyang Pharmaceutical Co., Ltd.), cross-linked carboxymethyl cellulose sodium (DuPont, USA), sodium stearyl fumarate (JRS, Germany).

[0098] Example 1 Preparation of pill core

[0099] The specific prescription of this embodiment is shown in Table 1.

[0100] Table 1

[0101] effect Material Dosage(g) Carrier Microcrystalline cellulose pellets 450 Active ingredients Tamsulosin Hydrochloride 9 Adhesives Hydroxypropyl methylcellulose 18 Solvents 95% ethanol 475 Solvents Purified water 120

[0102] Preparation process: 9g of tamsulosin hydrochloride and 18g of hypromellose (DuPont, USA) were dissolved in a mixture of 475g of 95% ethanol and 120g of purified water (80v / v% ethanol-water). 450g of microcrystalline cellulose pellets (made by JRS, Germany, D90 is about 200μm) were placed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) and coated by the Wurster bottom spray method (inlet air temperature 40-50℃, inlet air volume 20-80m 3 / h, spray liquid amount of 1-20g / min, atomization pressure of 1.0-2.5bar, material temperature of 25-45°C), to obtain tamsulosin-containing pellet cores.

[0103] Content detection: The content (i.e., drug application rate) was measured using the "General Rules of the Chinese Pharmacopoeia 0941 Content Uniformity Test Method" and was found to be 99.5%, A+2.2S=4.76, with a high drug application rate and good uniformity.

[0104] Example 2 Preparation of sustained-release pellet core

[0105] The specific prescription of this embodiment is shown in Table 2.

[0106] Table 2

[0107] effect Material Dosage(g) Active ingredients Tamsulosin hydrochloride containing pellet core 450 Sustained release materials Ethyl cellulose 35 Porogen Hydroxypropyl methylcellulose 10 Solvents 95% ethanol 1570 Solvents Purified water 390

[0108] Preparation process: 10 g of hydroxypropyl methylcellulose (DuPont, USA) and 35 g of ethyl cellulose (DuPont, USA) were dissolved in a mixture of 1570 g of 95% ethanol and 390 g of purified water (80 v / v% ethanol-water). 450 g of the pill cores in Example 1 were placed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) and coated by the Wurster bottom spray method (inlet air temperature 40-50°C, inlet air volume 20-80 m 3 / h, spray liquid amount of 1-15g / min, atomization pressure of 1.0-2.5bar, material temperature of 25-45°C), to obtain tamsulosin sustained-release pellet cores.

[0109] As described in CN108066304A, ethyl cellulose is crushed and then prepared into a suspension in water for sustained-release coating. After repeating the operation, it was found that the sustained-release pellets prepared by such coating method could not achieve the sustained-release effect claimed in the patent.

[0110] The content was measured by the "Chinese Pharmacopoeia General Rules 0941 Content Uniformity Test Method" to be 99.7%, A+2.2S=5.28, with good uniformity, and the pellet core did not lose content during the coating process. The dissolution data in pH 6.8 medium was measured by the "Chinese Pharmacopoeia General Rules 0931 Dissolution and Release Determination Method", and the results are shown in Table 12. Figure 1 .

[0111] Example 3 Preparation of enteric-coated pellet core

[0112] The specific prescription of this embodiment is shown in Table 3.

[0113] Table 3

[0114] effect Material Dosage(g) Active ingredients Tamsulosin Hydrochloride Sustained Release Pellets 450 Sustained release materials Aquacoat 150 Enteric Coated Materials Eudragit L30D55 400 Enteric Coated Materials Eudragit NM30D 50 Plasticizers Triethyl citrate 5 Anti-adhesive talcum powder 15 Solvents Purified water 600

[0115] Preparation process: 15g of talcum powder (Guangxi Longsheng Huamei Talc Development Co., Ltd.), 150g of ethyl cellulose aqueous dispersion (Aquacoat ECD-30, DuPont, USA), 400g of methacrylic acid-ethyl acrylate copolymer aqueous dispersion (Eudragit L30D55, Evonik, Germany), 50g of ethyl acrylate-methyl methacrylate copolymer aqueous dispersion (Eudragit NM30D, Evonik, Germany), and 5g of triethyl citrate (Senfilx, Morimura Shoji Co., Ltd.) were added to 600g of purified water to prepare an enteric coating solution. 450g of the sustained-release pellet core in Example 2 was placed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) and coated by the Wurster bottom spray method (inlet air temperature 30-60°C, inlet air volume 20-80m 3 / h, spray liquid amount of 1-20g / min, atomization pressure of 1.0-2.5bar, material temperature of 25-40°C), to obtain tamsulosin enteric-coated pellet cores.

[0116] The content was measured to be 99.7% by using the "Chinese Pharmacopoeia General Rules 0941 Content Uniformity Test Method" and the dissolution data in pH 6.8 medium and pH 1.2 medium were measured by the "Chinese Pharmacopoeia General Rules 0931 Dissolution and Release Determination Method". The results are shown in Table 12-13. Figure 2-3 .

[0117] Example 4 Preparation of Tamsulosin Hydrochloride Orally Disintegrating Sustained-Release Tablets

[0118] The specific prescription of this embodiment is shown in Table 4.

[0119] Table 4

[0120]

[0121]

[0122] Preparation process: 84.2 g of the enteric-coated pellet core in Example 3, 600 g of mannitol (Roquette Management (Shanghai) Co., Ltd.), 245 g of lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), and 12.8 g of cross-linked sodium carboxymethyl cellulose (DuPont, USA) were top-sprayed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) with a 25 wt% aqueous solution containing 50 g of maltose (Hunan Jiudian Hongyang Pharmaceutical Co., Ltd.) (inlet air temperature 80 ° C, air volume 40-90 m 3 / h, spray liquid volume of 10-40g / min, atomization pressure of 0.5-2.0bar, material temperature of 25-40℃, spray cycle: spray 2min-dry 1min), after spraying, it is dried to control the final moisture content to 0.5-1.5%, and then the obtained granules are sized using a 1000μm sieve, and 8g of sodium stearyl fumarate (JRS Company, Germany) is added thereto and mixed.

[0123] The above composition was compressed using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) with a main compression force of 2 KN and a filling depth of 6.5-7.8 mm to obtain tablets each containing 0.2 mg of tamsulosin, a tablet weight of 200 mg, and a hardness of 2.0 kp. During the entire tablet preparation process (i.e., granulation and tableting), the relative humidity of the environment was controlled at 55.0%.

[0124] Quality inspection: The newly compressed tablets were tested for 99.7% content by the "Chinese Pharmacopoeia General Rules 0941 Content Uniformity Test Method", and the "Chinese Pharmacopoeia General Rules 0923 Tablet Friability Test Method" and "General Rules 0921 Disintegration Time Test Method" were used to check their friability and disintegration time. The "Chinese Pharmacopoeia General Rules 0832 Moisture Determination Method Second Method - Drying Method" was used to measure the moisture content of the dried granules, total mixed powder, mixed powder during tableting and finished tablets. The finished tablets were placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and then samples were taken respectively. The friability and disintegration time were tested according to the above test methods, and the hardness and moisture changes were tested at the same time. The results are shown in Table 7. The results of the impact on the disintegration time are shown in Table 8.

[0125] The operation in this example was repeated several times, and the dissolution behaviors of multiple batches in different pH media were basically consistent, showing good reproducibility. The specific data are as follows:

[0126] Table 5 Dissolution reproducibility results in pH 6.8 medium

[0127] Batch No. / Time (min) 15 30 60 90 120 180 240 Reference preparation 6 29 57 69 76 84 88 Reproduce Batch 1 9 27 55 70 79 86 90 Reproduce Batch 2 11 25 56 72 78 85 89 Reproduce Batch 3 7 28 59 72 79 88 91

[0128] Table 6 Dissolution reproducibility results in pH 1.2 medium

[0129] Batch No. / Time (min) 30 60 90 120 Reference preparation 1 2 4 7 Reproduce Batch 1 0 1 4 7 Reproduce Batch 2 1 1 3 8 Reproduce Batch 3 2 2 5 9

[0130] Example 5 Preparation of Tamsulosin Hydrochloride Orally Disintegrating Sustained-Release Tablets in a High Humidity Environment

[0131] The formulation composition and preparation process were consistent with those in Example 4. During the entire tablet preparation process (ie, granulation and tableting), the relative humidity of the environment was controlled at 68.7%.

[0132] Quality inspection: The newly compressed tablets were inspected for friability and disintegration time using the "Chinese Pharmacopoeia General Rules 0923 Tablet Friability Test Method" and "General Rules 0921 Disintegration Time Test Method" respectively, and the "Chinese Pharmacopoeia General Rules 0832 Moisture Determination Method Second Method - Drying Method" was used to measure the moisture content of the dried granules, total mixed powder, mixed powder during tableting, and finished tablets. The finished tablets were placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and then samples were taken. The friability and disintegration time were tested according to the above test methods, and the hardness and moisture changes were tested at the same time. The results are shown in Table 7. The results of the impact on the disintegration time are shown in Table 8.

[0133] Example 6 Preparation of Tamsulosin Hydrochloride Orally Disintegrating Sustained-Release Tablets in a Low Humidity Environment

[0134] The formulation composition and preparation process were consistent with those in Example 4. During the entire tablet preparation process (ie, granulation and tableting), the relative humidity of the environment was controlled at 40.8%.

[0135] Quality inspection: The newly compressed tablets were inspected for friability and disintegration time using the "Chinese Pharmacopoeia General Rules 0923 Tablet Friability Test Method" and "General Rules 0921 Disintegration Time Test Method" and the "Chinese Pharmacopoeia General Rules 0832 Moisture Determination Method Second Method - Drying Method" was used to determine the moisture content of the dried granules, total mixed powder, mixed powder during tableting, and finished tablets. The finished tablets were placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and then samples were taken to test their friability and disintegration time according to the above test methods, and the hardness and moisture changes were also tested. The results are shown in Table 7. Figures 4 to 6 The results of the effects on disintegration time are shown in Table 8.

[0136] In the investigation of the effect of humidity on tablet hardness during different preparation processes (i.e., granulation and tableting), within the humidity range of about 40% to 70%, it is easy to achieve that the orally disintegrating sustained-release tablets of tamsulosin hydrochloride have good hardness and friability by simply adjusting the humidity range, among which Example 4 (55.0% relative humidity) has excellent disintegration performance.

[0137] Table 7 Effect of different environmental humidity on tablet hardness and moisture

[0138]

[0139]

[0140] Table 8 Effect of different environmental humidity on tablet disintegration time

[0141]

[0142] Example 7 Improvement of tablet hardness by controlling environmental humidity during tablet compression

[0143] The specific prescription of this embodiment is shown in Table 9.

[0144] Table 9

[0145] effect Material Dosage(g) Active ingredients Tamsulosin Enteric Coated Pills 84.2 Fillers Mannitol 600 Fillers lactose 245 Adhesives maltose 50 Disintegrants Croscarmellose Sodium 12.8 Lubricants Sodium stearyl fumarate 8 Solvents Purified water 150

[0146] Usually, the weather in the north is dry in winter and the ambient humidity is relatively low. In this case, only controlling the ambient humidity during tableting can also achieve the purpose of increasing the tablet hardness. The specific operation is as follows:

[0147] Ambient temperature: 18°C, ambient humidity: 23.6%, and the humidity of the environment during the granulation process was not controlled. Preparation process: 84.2 g of the enteric-coated pellet core in Example 3, 600 g of mannitol (Roquette Management (Shanghai) Co., Ltd.), 245 g of lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), and 12.8 g of cross-linked sodium carboxymethyl cellulose (DuPont, USA) were top-sprayed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) with a 25 wt% aqueous solution containing 50 g of maltose (Hunan Jiudian Hongyang Pharmaceutical Co., Ltd.) (inlet air temperature 80°C, inlet air volume 40-90 m 3 / h, spray liquid volume of 10-40g / min, atomization pressure of 0.5-2.0bar, material temperature of 25-40℃, spray cycle: spray 2min-dry 1min), after spraying, it is dried to control the final moisture content to 0.5-1.5%, and then the obtained granules are sized using a 1000μm sieve, and 8g of sodium stearyl fumarate (JRS Company, Germany) is added thereto and mixed.

[0148] The rotary tablet press was wrapped with a polyethylene bag, and the large plate of the tablet press was humidified with a humidifier so that the tablet pressing process was in a high humidity environment (50.0%). The above composition was then tableted using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) with a main pressing force of 2KN and a filling depth of 6.5-7.8mm to obtain tablets containing 0.2mg of tamsulosin per tablet, a tablet weight of 200mg, and a hardness of 2.0kp.

[0149] The content of the newly compressed tablets was measured to be 99.7% using the "Chinese Pharmacopoeia General Chapter 0941 Content Uniformity Test Method".

[0150] The tamsulosin hydrochloride orally disintegrating sustained-release tablets prepared in Example 4 and Example 7 were subjected to quality inspection.

[0151] Quality inspection: The friability and disintegration time were inspected according to the "General Rules of the Chinese Pharmacopoeia 0923 Tablet Friability Inspection Method" and "General Rules 0921 Disintegration Time Inspection Method". The finished tablets were placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, and then samples were taken. The friability and disintegration time were tested according to the above test methods, and the hardness change was tested at the same time. The comparison results with Example 4 are shown in Table 10. Figure 7 shown.

[0152] By comparing Examples 4 and 7, it can be seen that under limited experimental conditions, the effect of improving tablet hardness and friability can be achieved simply by controlling the ambient humidity during the tableting process.

[0153] Table 10 Comparison of tablet hardness and friability between Example 4 and Example 7

[0154]

[0155] Example 8 Using maltitol as granulation binder

[0156] The specific prescription of this example is shown in Table 11.

[0157] Table 11

[0158] effect Material Dosage(g) Active ingredients Tamsulosin Enteric Coated Pills 84.2 Fillers Mannitol 600 Fillers lactose 245 Adhesives Maltitol 50 Disintegrants Croscarmellose Sodium 12.8 Lubricants Sodium stearyl fumarate 8 Solvents Purified water 150

[0159] Preparation process: 84.2 g of the enteric-coated pellet core in Example 3, 600 g of mannitol (Roquette Management (Shanghai) Co., Ltd.), 245 g of lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), and 12.8 g of cross-linked sodium carboxymethyl cellulose (DuPont, USA) were top-sprayed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) with a 25 wt% aqueous solution containing 50 g of maltitol (inlet air temperature 80 ° C, inlet air volume 40-90 m 3 / h, spray liquid volume of 10-40g / min, atomization pressure of 0.5-2.0bar, material temperature of 25-40℃, spray cycle: spray 2min-dry 1min), after spraying, it is dried to control the final moisture content to 0.5-1.5%, and then the obtained granules are sized using a 1000μm sieve, and 8g of sodium stearyl fumarate (JRS Company, Germany) is added thereto and mixed.

[0160] The above composition was tableted using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) with a main pressing force of 2KN and a filling depth of 6.5-7.8mm to obtain tablets containing 0.2mg of tamsulosin per tablet, a tablet weight of 200mg, and a hardness of 1.0-2.0kp. During the entire tablet preparation process (i.e., granulation and tableting), the relative humidity of the environment was controlled at 55.0%.

[0161] After the finished sheets were placed in an environment with a relative humidity of less than 10% for 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, and 96 h, samples were taken for subsequent experiments.

[0162] Comparative Example 1 Preparation of reference reagent

[0163] 1. Material information:

[0164] Tamsulosin hydrochloride, hydroxypropyl methylcellulose (TC5E, manufactured by Shin-Etsu Chemical), Celphere 102 (manufactured by Asahi Kasei Corporation, average particle size of about 127 μm, particle size of about 50-150 μm), ethyl cellulose (Niksin Chemical), Aquacoat (trade name, manufactured by Asahi Kasei Corporation), Eudragit L30D55 ​​(trade name, manufactured by Rohm), Eudragit NE30D (trade name, manufactured by Rohm), mannitol (manufactured by Towa Chemical Industry Co., Ltd.), lactose (manufactured by Domomilk) in a fluidized bed granulator (Freund Sangyo, FLO-5), maltose (Hayashibara Shoji Co., Ltd., trade name: Sunmalt S), calcium stearate.

[0165] 2. Process information:

[0166] 80 g of tamsulosin hydrochloride and 80 g of hydroxypropyl methylcellulose (TC5E, manufactured by Shin-Etsu Chemical) were dissolved in a mixed solution of 304 g of purified water and 2736 g of methanol. 4000 g of Celphere 102 (manufactured by Asahi Kasei Corporation, average particle size of about 127 μm, particle size of about 50-150 μm) was placed in a fluidized bed granulator (Freund Industries, FLO-5) and coated with the solution by side spraying (spraying liquid volume of 100 g / min, spraying air pressure of 4 kg / cm 2 , product temperature is 40°C, and suction temperature is 80°C) to obtain tamsulosin hydrochloride particles.

[0167] In addition, 533 g of ethyl cellulose (Nissin Chemical) and 187 g of hydroxypropyl methyl cellulose (TC5E, trade name, manufactured by Shin-Etsu Chemical) were dissolved in a mixed solution of 698 g of purified water and 22582 g of methanol. 4000 g of tamsulosin hydrochloride particles were placed in a fluidized bed granulator (Freund Industries, FLO-5) and coated with the solution by a side spray method (spraying liquid volume of 40 g / min, spraying air pressure of 4 kg / cm 2 , product temperature is 50°C, and inhalation temperature is 60°C) to obtain sustained-release pellet cores.

[0168] 4000 g of the sustained-release pellet cores were placed in a fluidized bed granulator (FLO-5 manufactured by Freund Industries) and coated with a mixed solution of 2000 g of Aquacoat (trade name, manufactured by Asahi Kasei Corporation), 4000 g of Eudragit L30D55 ​​(trade name, manufactured by Rohm Co., Ltd.), 667 g of Eudragit NE30D (trade name, manufactured by Rohm Co., Ltd.), and 6667 g of purified water by a side spray method (spray liquid volume of 40 g / min, spray air pressure of 4 kg / cm 2, product temperature is 40°C, and inhalation temperature is 60°C) to obtain enteric-coated sustained-release pellet cores.

[0169] 368 g of the enteric sustained-release pellet core, 2560 g of mannitol (manufactured by Towa Chemical Industry Co., Ltd.), and 640 g of lactose (manufactured by Domomilk) were granulated in a fluidized bed granulator (manufactured by Freund Industry, FLO-5) using a 40% w / w aqueous solution containing 400 g of maltose (manufactured by Hayashibara Shoji Co., Ltd., trade name: Sunmalt S) (spraying liquid volume of 200 g / min, spraying air pressure of 1.5 kg / cm 2 , product temperature is 29° C., inhalation temperature is 80° C., spray cycle: 10 seconds spraying-30 seconds drying), to obtain the composition of the present invention.

[0170] Then, 32 g of calcium stearate was added to the obtained composition, mixed, and then a rotary tablet press was used with a tableting pressure of 100 kg / punch and an initial hardness of 1.0 kp to produce 200 mg tablets containing 0.2 mg of tamsulosin hydrochloride per tablet. The tablets were stored in a constant temperature and humidity machine (manufactured by Tabai Spec, PR-35C) at 25°C / 75% RH for 18 hours. Afterwards, they were dried at 30°C and 40% RH for 3 hours. The hardness of the obtained tablets was 5.9 kp (n=5), the abrasion was 0.8% (100 turns), and the oral disintegration time was 20 seconds (n=3). The evaluation result of the content uniformity was CV%=2.1%.

[0171] The sustained-release pellet cores prepared in Example 2, the enteric-coated pellet cores prepared in Example 3, and the reference reagent in Comparative Example 1 were used for dissolution testing.

[0172] 3. Dissolution determination: According to the "Chinese Pharmacopoeia General Rules 0931 Dissolution and Release Determination Method", the dissolution data of Comparative Example 1, Example 2, and Example 3 in pH 1.2 and pH 6.8 media were determined. For sustained-release tablets, they enter the intestine from the stomach 30 to 120 minutes after swallowing, and their sustained release is mainly in the intestine. In the pH 1.2 medium, Example 3 has no drug dissolution within 0 to 90 minutes, and the dissolution rate at 120 minutes is only half of that of the reference agent. It can be seen that compared with the reference preparation, Example 3 has a stronger gastric acid resistance, its active ingredients are less released in the stomach, and more active ingredients can be retained for release in the intestine.

[0173] In the medium of pH 6.8, compared with the reference preparation, the sustained-release pellet core prepared in Example 2 and the enteric-coated pellet core prepared in Example 3 both have excellent sustained-release effects, which further proves that the fact that Example 3 has almost no release in the medium of pH 1.2 is not due to the excessively thick enteric coating film, but due to the preparation process, it has better acid resistance and better dissolution release than the reference preparation. As shown in Tables 12-13, Figure 1-3 shown.

[0174] Table 12 Release of reference preparation and Examples 2 and 3 in pH 6.8 medium

[0175] Batch No. / Time (min) 15 30 60 90 120 180 240 Reference preparation 6 29 57 69 76 84 88 Example 2 14 30 56 71 78 87 89 Example 3 6 25 54 68 76 83 87

[0176] Table 13 Release of reference preparation and Example 3 in pH 1.2 medium

[0177] Batch No. / Time (min) 30 60 90 120 Reference preparation 1 2 4 7 Example 3 0 0 0 4

[0178] 4. Effect of different solvents on drug application rate

[0179] The present invention further tests the solubility of tamsulosin hydrochloride in ethanol-water solution and methanol-water solution of different concentrations, and the corresponding drug application rate. The results are shown in Tables 14 and 15.

[0180] Table 14 Solubility of tamsulosin hydrochloride in ethanol-water solution and methanol-water solution at different concentrations

[0181] Solvent (v / v) Amount of solvent required to dissolve 1g (ml) Solubility water 84.5 Slightly soluble 70% ethanol 29.64 Dissolve 80% ethanol 25.30 Dissolve 90% ethanol 42.30 Slightly soluble 99.5% ethanol (absolute ethanol) 2100 Very slightly soluble 80% Methanol 18.84 Dissolve 90% Methanol 20.51 Dissolve 99.9% methanol (anhydrous methanol) 47.79 Slightly soluble

[0182] Table 15 Drug application rate of tamsulosin hydrochloride in ethanol-water solution and methanol-water solution of different concentrations

[0183] Solvents Drug application rate % Remark 70% ethanol 86.9 / 80% ethanol 99.3 Solvent used in Example 1 90% ethanol 93.4 / 80% Methanol 92.7 / 90% Methanol 90.2 Solvent used in reference preparation (Comparative Example 1)

[0184] The results show that:

[0185] The reference preparation (Comparative Example 1) uses a 90% methanol-water solution to dissolve tamsulosin hydrochloride for drug application, while Example 1 uses an 80% ethanol-water solution as a solvent. It can be seen from the above table that the solubility of tamsulosin hydrochloride in the two concentrations of solvents (90% methanol-water, 80% ethanol-water) is not much different.

[0186] The prescription of the reference preparation (Comparative Example 1) was repeated, and the drug loading rate of the obtained pill core was 90.2%, which was much lower than that of Example 1. It can be seen that compared with the prescription and process of the reference preparation (Comparative Example 1), Example 1 has greater advantages.

[0187] In addition, the preparation of the reference reagent requires a large amount of methanol, which is a highly toxic volatile liquid and has extremely high safety issues during the production process. However, Example 1 uses ethanol to replace methanol, which has higher safety.

[0188] 5. Effect of different solvents on coating effect

[0189] The results are shown in Table 16. The reference preparation (Comparative Example 1) uses methanol, which is more harmful, and the coating time is longer, while Example 2 uses ethanol, which is less harmful, and the coating time is shorter. The sustained-release effect of the sustained-release coating film is basically similar to that of the reference preparation (Comparative Example 1). It can be seen that Example 2 has obvious advantages under the premise of ensuring the quality of the sustained-release coating film.

[0190] Table 16 Prescription and coating time used for reference preparation (Comparative Example 1) and Example 2

[0191]

[0192]

[0193] Comparative Example 2 Preparation by direct pressing of powder

[0194] The specific prescription of this comparative example is shown in Table 17.

[0195] Table 17

[0196] effect Material Dosage(g) Active ingredients Tamsulosin Enteric Coated Pills 84.2 Fillers Mannitol 50C 780.8 Fillers Microcrystalline Cellulose PH102 50 Disintegrants Croscarmellose Sodium 75 Lubricants Sodium stearyl fumarate 10

[0197] Preparation process: Weigh 84.2g of the enteric-coated pellet core in Example 3, 780.8g of mannitol (50C, Roquette Management (Shanghai) Co., Ltd.), 50g of microcrystalline cellulose (model: PH102, manufactured by Anhui Shanhe Pharmaceutical Excipients Co., Ltd.), 75g of cross-linked carboxymethyl cellulose sodium (DuPont, USA), mix for 10min to complete the main mixing, then weigh 10g of sodium stearyl fumarate (JRS, Germany), mix for 10min to complete the total mixing. The above composition is compressed using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) with a main pressing pressure of 2KN and a filling depth of 6.2-7.0mm to prepare tablets containing 0.2mg tamsulosin per tablet, a tablet weight of 200mg, and a hardness of 2.0kp.

[0198] The friability and disintegration time of Comparative Example 2 were tested using the "General Rules 0923 Tablet Friability Test Method" and the "General Rules 0921 Disintegration Time Test Method" of the Chinese Pharmacopoeia. The friability was 2.58% (100 turns) and the disintegration time was 33s.

[0199] The reference reagent in Comparative Example 1, the powder direct compression tablet in Comparative Example 2, and the tamsulosin hydrochloride orally disintegrating sustained-release tablets prepared in Example 4 were taken for comparative testing. The dissolution curve results of the reference preparation in Comparative Example 1, the powder direct compression tablet in Comparative Example 2, and Example 4 in pH 6.8 medium and pH 1.2 medium are shown in Tables 18-19, Figure 8 , Fig. 9 shown.

[0200] Results: Wet granulation can protect the functional coating of the pellet core, while the sustained release effect and acid resistance of the tablets prepared by powder direct compression process are both poor. Powder direct compression only showed a good disintegration effect, and performed poorly in terms of dissolution, acid resistance, friability, etc. The specific results are as follows:

[0201] Table 18 Dissolution results in pH 6.8 medium

[0202]

[0203]

[0204] Table 19 Dissolution results in pH 1.2 medium

[0205] Batch No. / Time (min) 30 60 90 120 Reference preparation 1 2 4 7 Example 4 0 1 4 7 Comparative Example 2 5 7 12 17

[0206] Comparative Example 3 Orally disintegrating tablet coating

[0207] The specific prescription of this comparative example is shown in Table 20.

[0208] Table 20

[0209]

[0210] Preparation process: Weigh 1.0 g of mannitol (50C, Roquette Management (Shanghai) Co., Ltd.) and 4 g of hypromellose (DuPont, USA), dissolve them in 95.0 g of purified water to prepare a 5% concentration coating solution, and use a coating machine (O'Hara Technologies Inc.) to coat the finished tablets in Example 4. Set the inlet temperature to 35°C, the outlet temperature to 30°C, the coating pan speed to 10 rpm, the peristaltic pump opening to 2.6%, the main spray pressure and the test spray pressure of the spray gun to 0.30 bar, and the coating weight gain to 1%.

[0211] Results: After coating the plain tablets, the hardness increased from 2.0 kp to 3.5 kp, the abrasion was 0.0% (100 revolutions), the disintegration time slowed down from 49 s to 55 s, and the disintegration effect became worse. Compared with Example 4, the process was complicated and the effect was limited.

[0212] Comparative Example 4: Maltose crystallization--Preparation of tamsulosin hydrochloride orally disintegrating sustained-release tablets

[0213] In view of the description in CN1473035B that a newly compressed tablet (1.0 kp) is placed in a constant temperature and humidity drying oven at 25°C / 75% RH for 18 hours, and then dried at 30°C / 40% RH for 3 hours, the tablet hardness can be increased to 5.9 kp. Using a similar operation method, the following comparative example was carried out.

[0214] The specific prescription of this comparative example is shown in Table 21.

[0215] Table 21

[0216]

[0217]

[0218] Preparation process: 84.2 g of the enteric-coated pellet core in Example 3, 600 g of mannitol (Roquette Management (Shanghai) Co., Ltd.), 245 g of lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), and 12.8 g of cross-linked sodium carboxymethyl cellulose (DuPont, USA) were top-sprayed in a fluidized bed (Chuangzhi Technology, FLZB-3.0) with a 25 wt% aqueous solution containing 50 g of maltose (Hunan Jiudian Hongyang Pharmaceutical Co., Ltd.) (inlet air temperature 80 ° C, air volume 40-90 m 3 / h, spray liquid volume of 10-40g / min, atomization pressure of 0.5-2.0bar, material temperature of 25-40℃, spray cycle: spray 2min-dry 1min), after spraying, it is dried to control the final moisture content to 0.5-1.5%, and then the obtained granules are sized using a 1000μm sieve, and 8g of sodium stearyl fumarate (JRS Company, Germany) is added thereto and mixed.

[0219] The above composition was compressed using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) with a main compression force of 2KN and a filling depth of 6.5-7.8mm to obtain tablets each containing 0.2mg of tamsulosin, with a tablet weight of 200mg and a hardness of 2.0kp.

[0220] The tablets were stored in a dryer with a humidity of 75% and an ambient temperature of 20°C. After storage for 16 hours, they were placed in an electric blast drying oven (Changzhou Jeboson Instrument Co., Ltd., DHG-9030A) and dried at 40°C for 2 hours.

[0221] Results: The technical solution for improving tablet hardness claimed in CN1473035B was reproduced, that is, the hardness of the tablets obtained after moisture absorption and drying was only increased from 1.0 kp to 1.8 kp.

[0222] The moisture absorption and drying in this comparative example is an operation performed after the tableting process is completed. When the tablet pressing is completed, the change in humidity no longer affects the inside of the tablet, and the synergistic effect between the raw and auxiliary materials cannot be achieved, and it does not have the technical effect of improving the overall hardness of the tablet.

[0223] Comparative Example 5: Physical mixture of tamsulosin hydrochloride without maltose

[0224] The specific prescription of this comparative example is shown in Table 22.

[0225] Table 22

[0226] effect Material Dosage(g) Active ingredients Tamsulosin Enteric Coated Pills 84.2 Fillers Mannitol 650 Fillers lactose 245 Disintegrants Croscarmellose Sodium 12.8 Lubricants Sodium stearyl fumarate 8

[0227] Preparation process: 84.2 g of the enteric-coated microcapsules in Example 3, 650 g of mannitol (Roquette Management (Shanghai) Co., Ltd.), 245 g of lactose (Jiangsu Daoning Pharmaceutical Co., Ltd.), 12.8 g of cross-linked sodium carboxymethyl cellulose (DuPont, USA), and 8 g of sodium stearyl fumarate (JRS, Germany) were mixed to prepare a physical mixture that does not contain maltose.

[0228] The tablets of Example 4, Comparative Example 4 and Comparative Example 5 were tested for maltose crystal form.

[0229] Results: The tablet hardness of Comparative Example 4 was only increased from 1.0 kp to 1.8 kp. In Comparative Example 4, there was no obvious crystal transformation of maltose before and after the entire preparation process, and the hardness could not be increased as described in the preparation method of patent document CN1473035B, that is, the tablet hardness could be increased from 1.0 kp to 5.9 kp by the operation of absorbing moisture and then drying the tablet (maltose crystal transformation). Therefore, the improvement of tablet hardness is not caused by the transformation of maltose crystal form.

[0230] The crystal form test results are as follows Fig.10 shown.

[0231] Comparative Example 6 Low Humidity Tableting

[0232] This comparative example is similar to Example 4, except that the relative humidity of the environment is controlled to be 23.2% during the preparation process.

[0233] Comparative Example 7 High Humidity Tableting

[0234] This comparative example is similar to comparative example 4, except that the relative humidity of the environment is controlled to be 74.3% during the preparation process.

[0235] The orally disintegrating sustained-release tablets of tamsulosin hydrochloride prepared in Example 7, Comparative Example 6 and Comparative Example 7 were tested for hardness.

[0236] The tablets obtained in Comparative Example 6 cannot achieve the purpose of increasing hardness after being stored in an environment with a relative humidity of less than 10% for a certain period of time (such as 18 hours, 24 hours, or 48 hours).

[0237] Comparative Example 7 could only proceed to the spray drying stage. Since the prepared granules were too large and too hard (the prepared granules could not be smoothly sized by a screen or a granulator), the subsequent sieving, granulating and tableting operations could not be performed.

[0238] Conclusion: Compared with Example 7, in Comparative Examples 6 and 7, during the spray granulation process, the ambient humidity cannot be too high (such as greater than 70%), otherwise the granulation operation cannot be carried out smoothly. During the tableting process, the ambient humidity needs to be maintained within a certain range to achieve the increase in tablet hardness, that is, too high or too low tableting humidity cannot improve the tablet hardness.

[0239] Comparative Example 8: Glucose as Granulation Binder

[0240] This comparative example is similar to Example 4, except that: a 25wt% aqueous solution containing 100g of glucose is used for top spray granulation. Tablets containing 0.2mg of tamsulosin, weighing 200mg, and having a hardness of 1.0-2.0kp are prepared. The finished tablets are placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and samples are taken respectively.

[0241] Comparative Example 9: Sucrose as Granulation Binder

[0242] This comparative example is similar to Example 4, except that: a 25wt% aqueous solution containing 100g of sucrose is used for top spray granulation. Tablets containing 0.2mg of tamsulosin, weighing 200mg, and having a hardness of 1.0-2.0kp are prepared. The finished tablets are placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and then samples are taken respectively.

[0243] Comparative Example 10: Using xylitol as a granulation binder

[0244] This comparative example is similar to Example 4, except that a 25 wt% aqueous solution containing 100 g of xylitol is used for top spray granulation. Granulation and tableting operations cannot be performed normally using xylitol.

[0245] Comparative Example 11 does not use granulation binder

[0246] This comparative example is similar to Example 4, except that: no granulation binder is used, only purified water is used for top spray granulation, and the amount of the binder (100g) is replaced by mannitol. Tablets containing 0.2mg tamsulosin per tablet, weighing 200mg, and having a hardness of 1.0-2.0kp are prepared. The finished tablets are placed in an environment with a relative humidity of less than 10% for 12h, 24h, 36h, 48h, 60h, 72h, 84h, and 96h, and then samples are taken respectively.

[0247] The orally disintegrating sustained-release tablets of tamsulosin hydrochloride prepared in Comparative Examples 8, 9, 11 and Examples 4 and 8 and stored for different times were tested for hardness.

[0248] Results: After the tablets were stored for a certain period of time according to the above operation, only maltose and maltitol can improve the hardness of the tablets, and the other excipients have no obvious effect. According to the "Chinese Pharmacopoeia General Chapter 0921 Disintegration Time Test Method", except for maltitol, the disintegration time of tablets made with other different adhesives was not affected, which was 40s to 50s. Tablets using maltitol cannot disintegrate in the disintegrator, but it can still be determined that maltitol plays an important role in increasing the hardness of tablets. The hardness changes are shown in Table 23, Fig.11 shown.

[0249] Table 23 Effect of different binders on tablet hardness

[0250]

[0251] Comparative Example 12 Effect of different lubricants on disintegration performance

[0252] This embodiment is similar to embodiment 4, except that the lubricant used is magnesium stearate or calcium stearate or stearic acid or a mixture of magnesium stearate and colloidal silicon dioxide.

[0253] The disintegration time of the newly compressed tablets was tested using the "Chinese Pharmacopoeia General Chapter 0921 Disintegration Time Test Method", and the results are shown in the following table:

[0254] Table 24 Effect of different lubricants on disintegration performance

[0255]

[0256]

[0257] Experimental results: The use of hydrophilic lubricant (hard sodium fumarate) can effectively improve the disintegration time of tablets and avoid the disintegration performance of orally disintegrating tablets in water being affected by hydrophobic excipients.

[0258] Comparative Example 13 Effect of main compression pressure on tablet hardness and acid resistance

[0259] The total mixed granules prepared in Example 4 were tableted using a rotary tablet press (Chuangbo Jiawei Technology, C&C800) under different main pressing pressures (1KN, 2KN, 3KN, 4KN, 5KN) to obtain tablets containing 0.2 mg of tamsulosin per tablet and weighing 200 mg. The relative humidity of the environment was controlled at about 55% during the preparation process.

[0260] Results: The newly compressed tablets were tested for friability and disintegration time using the Chinese Pharmacopoeia General Rules 0923 Tablet Friability Test Method and the Chinese Pharmacopoeia General Rules 0921 Disintegration Time Test Method. The dissolution data in pH 6.8 medium and pH 1.2 medium were measured using the Chinese Pharmacopoeia General Rules 0931 Dissolution and Release Determination Method as shown in Tables 25 and 26. Fig.12 , 13 As shown in the figure, it can be seen that excessive main pressure will damage the functional coating of the pellet core and fail to achieve the initial sustained release effect and acid resistance.

[0261] Table 25 Dissolution of tablets in pH 6.8 medium

[0262] Batch No. / Time (min) 15 30 60 90 120 180 240 Reference preparation 6 29 57 69 76 84 88 1KN 7 26 55 72 78 85 94 2KN 9 27 55 70 79 86 90 3KN 10 28 60 73 77 84 90 4KN 13 33 65 75 82 88 92 5KN 19 35 69 78 83 90 94

[0263] Table 26 Dissolution of tablets in pH 1.2 medium

[0264] Batch No. / Time (min) 30 60 90 120 Reference preparation 1 2 4 7 1KN 0 2 4 7 2KN 3 4 5 9 3KN 3 6 8 10 4KN 4 7 12 17 5KN 11 13 18 23

Claims

1. A method for improving tablet hardness, characterized in that: The following steps are involved: Tablets are pressed in a humidity range of 40-70%; The tablet contains maltose or a combination of its derivatives; The maltose derivative includes at least one of a hydrogenation product, a ketone product and an oxidation product of maltose.

2. The method according to claim 1, characterized in that: The tablets are dried after tableting; The drying time is 12 to 96 hours.

3. The method according to claim 2, characterized in that: The tabletting pressure is 1-4 KN.

4. The method according to claim 3, characterized in that: The tablet has one or more coating layers.

5. The method according to claim 4, characterized in that: The maltose or its derivative combination is added during granulation.

6. A tamsulosin hydrochloride orally disintegrating sustained-release tablet, characterized in that: It includes a pill core, a sustained-release layer, an enteric layer, and granulation excipients; The drug-containing pellet core comprises tamsulosin, a carrier, and a drug binder; and / or The sustained-release layer comprises a sustained-release material and a pore-forming agent, and the sustained-release layer is wrapped on the drug-containing pill core to obtain a sustained-release pill core; and / or The enteric layer comprises an enteric material, a plasticizer, and an anti-adhesive agent, and the enteric layer is wrapped on the sustained-release pill core to obtain an enteric-coated pill core; and / or The granulation excipients include fillers, disintegrants, lubricants, granulation binders; and / or The granulation binder comprises maltose or a combination of its derivatives; The tamsulosin hydrochloride orally disintegrating sustained-release tablets are prepared by using the method according to claim 1 to improve tablet hardness.

7. The orally disintegrating sustained-release tablet of tamsulosin hydrochloride according to claim 6, characterized in that: The enteric-coated pellet core comprises, by weight, 5 to 15 parts of tamsulosin, 300 to 600 parts of a carrier, and 10 to 25 parts of a drug binder; the sustained-release layer comprises, by weight, 20 to 55 parts of a sustained-release material and 5 to 20 parts of a pore-forming agent; and / or the enteric layer comprises, by weight, 350 to 1000 parts of an enteric material, 5 to 30 parts of a plasticizer, and 1 to 10 parts of an anti-adhesive agent; and / or The granulation auxiliary materials include, by weight, 300 to 550 parts of filler, 20 to 65 parts of granulation binder, 2 to 8 parts of disintegrant, and 2 to 5 parts of lubricant; The mass ratio of the granulation auxiliary material to the enteric-coated pill core is 60-120:700-1200.

8. The orally disintegrating sustained-release tablet of tamsulosin hydrochloride according to claim 7, characterized in that: The carrier comprises at least one of microcrystalline cellulose, starch, dextrin, mannitol, and anhydrous calcium hydrogen phosphate; and / or The drug binder comprises at least one of hydroxypropyl methylcellulose, hydroxypropyl cellulose and polyvinyl pyrrolidone; and / or The sustained-release material includes ethyl cellulose, cellulose acetate, polyacrylic acid resin; and / or The porogen includes at least one of hydroxypropyl methylcellulose, hydroxypropyl cellulose and polyvinyl pyrrolidone; and / or The enteric material comprises at least one of Aquacoat, Eudragit L30D55, and Eudragit NM30D; and / or The plasticizer includes triethyl citrate, diethyl phthalate, tributyl citrate, dibutyl sebacate, polyethylene glycol, glyceryl mono- and distearate; and / or The anti-sticking agent comprises talc; and / or The filler comprises at least one of mannitol and lactose; and / or The disintegrant comprises cross-linked carboxymethyl cellulose sodium; and / or The lubricant includes sodium stearyl fumarate.

9. The method for preparing the orally disintegrating sustained-release tamsulosin hydrochloride tablets according to any one of claims 6 to 8, comprising the following steps: 1) dissolving the active ingredient of the pill core and the drug binder in a mixture of ethanol and water, coating the carrier to obtain the pill core; 2) dissolving the sustained-release material and pore-forming agent of the sustained-release layer in a mixture of ethanol and water, coating the drug-containing pill core to obtain a sustained-release pill core; 3) dispersing the enteric material, plasticizer and anti-adherent agent of the enteric layer in purified water, coating the sustained-release pellet core to obtain the enteric-coated pellet core; 4) Mixing the filler and disintegrant in the granulation excipients with the enteric-coated pellet core, adding the granulation binder solution to granulate, sieving the granules, adding the lubricant to mix, and tableting; 5) drying for 12 to 96 hours to obtain; Preferably, the volume of ethanol in the ethanol-water mixture is 60-90%.

10. The preparation method according to claim 9, characterized in that: The steps 1) to 4) are performed in an environment with a relative humidity of 40 to 70%; The tabletting pressure is 1-4 KN.

Citation Information

Patent Citations

  • Tamsulosin orally disintegrating tablet composition with slow release performance

    CN108066304A

  • Method for improving hardness of orally disintegrating tablet and disintegrating orally disintegrating tablet, and positioning and releasing of orally disintegrating tablet

    CN108066305A

  • Compositions containing substained-release fine grains for tablets quickly disintegrable in oral cavity and process for producing same

    CN1473035B